Implementasi Moderasi Beragama dalam Membentuk Generasi Wasathiyah Siswa di Madrasah Aliyah Hidayatul Mubtadiin Sidoharjo Jati Agung Lampung Selatani - Dewi Syafitri Dwi Jayanti; Tamyis Tamyis; Endang Ekowati (Departement of Mathematics Education, 2024)
The objective of this study is to examine the role that religious moderation plays in shaping the wasathiyah generation of female students at Madrasah Aliyah Hidayatul Mubtadiin Sidoharjo Jati Agung South Lampung in 2023–2024, as well as the factors that encourage and hinder this role. This study takes a qualitative approach to its methodology. Data reduction, data presentation, and conclusion-making are the first steps in the data collection processes that use observation, interviews, and documentation. The study's findings come to this conclusion: The Wasathiyah Generation of Madrasah Aliyah Hidayatul Mubtadiin Sidoharjo Jati Agung South Lampung pupils is the result of the application of religious moderation values. When using the principles of religious moderation The Wasathiyah Generation of students is formed by Madrasahs through the application of three values of religious moderation: the attitudes of Tawassuth (Central), Tasamuh (Tolerance), and Syuro (Deliberation). This realization of the Wasathiyah Generation is in line with the teachings of the Qur'an and the Prophet's Sunnah. Madrasas play a significant role in religious education and serve as a platform for instilling the values of religious moderation in the Wasathiyah generation, which is a supporting element for religious moderation. establishing an accepting and tranquil community. Lack of knowledge about religious moderation—many students have a limited, textual comprehension that concentrates on literal religious norms and prohibitions—is the impediment to religious moderation in shaping the Wasathiyah generation. Because of this, they may be more susceptible to radical and extreme religious interpretations. Collaboration between the Ministry of Religion, Madrasas, Teachers, Parents, and the Community is needed to address these obstacles